Subiektywne teorie na temat uczenia się języka obcego studentów romanistyki - Pudo, Dorota (Neofilolog, 2017)
Research on subjective (implicit) theories, similarly to studies on other kinds of beliefs, has a rich tradition in the SLA field. This study presents the results of a survey conducted among 55 Romance Philology students, containing open-ended questions about different aspects of the language learning process: nature of the language itself, learner's personal attributes facilitating learning, effective learning activities, optimal learning environment, obstacles to learning, role played by other people. Due to the use of a qualitative methodology (open-ended questions), a large variety of different answers was collected. The data were analysed and divided into subject categories, and the answers falling into each category were counted in order to provide an overall view of the group's tendencies. The students' answers mainly confirm that they see learning a language as a long process demanding time and effort. Students' motivation and perseverance prove to be the most important factors whereas features such as intelligence or language aptitude are underestimated.